Holistic processing of human body postures: evidence from the composite effect - Willems, Sam; Vrancken, Leia; Germeys, Filip; Verfaillie, Karl (Frontiers in Psychology, 2014)
The perception of socially relevant stimuli (e.g., faces and bodies) has received considerable attention in the vision science community. It is now widely accepted that human faces are processed holistically and not only analytically. One observation that has been taken as evidence for holistic face processing is the face composite effect: Two identical top halves of a face tend to be perceived as being different when combined with different bottom halves. This supports the hypothesis that face processing proceeds holistically. Indeed, the interference effect disappears when the two face parts are misaligned (blocking holistic perception). In the present study, we investigated whether there is also a composite effect for the perception of body postures: Are two identical body halves perceived as being in different poses when the irrelevant body halves differ from each other? Both a horizontal (i.e., top-bottom body halves; Experiment 1) and a vertical composite effect (i.e., left-right body halves; Experiment 2) were examined by means of a delayed matching-to-sample task. Results of both experiments indicate the existence of a body posture composite effect. This provides evidence for the hypothesis that body postures, as faces, are processed holistically.